Influence of Regulatory Tax Changes on Business Strategies in the Telecommunications Industry - Rani Fitri (Manunggal Halim Jaya, 2024)
This qualitative study explores the influence of regulatory tax changes on business strategies in the telecommunications industry. The research aims to provide insights into the complex interplay between tax regulations, strategic decision-making, and industry dynamics within the telecommunications sector. Employing a systematic review and synthesis of scholarly literature, the research methodology involves comprehensive data collection, thematic analysis, and interpretation of findings. The results reveal that tax policies significantly shape telecommunications firms' cost structures, profitability, pricing strategies, and market positioning. Differential tax treatments, such as VAT exemptions and digital services tax rates, have profound implications for firms' strategic responses and competitive advantage. Moreover, the study highlights the importance of regulatory intelligence, agility, and flexibility in navigating regulatory complexities and optimizing firms' tax positions. The findings underscore the multifaceted nature of regulatory tax changes and their implications for business strategies, emphasizing the need for proactive assessment, adaptive responses, and industry engagement. This study contributes to a deeper understanding of the dynamic relationship between tax regulations and strategic decision-making in the telecommunications industry, informing evidence-based policymaking and managerial practices.